Implementation of Political Literacy to Improve Political Participation in Facing the 2024 Simultaneous Regional Head Elections: A Descriptive Study of PPKn Students of STKIP Pasundan - Sutanto, Hilman (SAINTIS Publishing, 2024)
The purpose of this study was to describe the perspectives of PPKn STKIP Pasundan Students regarding political literacy and the forms of political participation conveyed in the implementation of the 2024 simultaneous Pilkada. The research approach used a qualitative descriptive method. The results of the study obtained from interviews were analyzed and interpreted, so it can be concluded that political literacy is obtained by PPKn Students through political science courses through learning methods including lectures, presentations, discussions, literature studies, focus group discussions (FGD), field studies and individual assignments. The learning media used by Students in increasing political literacy are predominantly obtained through digital media or social media such as online news portals, YouTube, Facebook and Instagram. The description of the form of political participation of PPKn STKIP Pasundan Students is in accordance with the hierarchy of political participation, namely the higher the hierarchy of participation, the less the number of Student involvement and the lower the hierarchy of political participation, the greater the Student involvement. The perspective of PPKn STKIP Pasundan Students on the simultaneous Pilkada is equality in providing political rights, the opportunity to expand knowledge and freedom to convey political arguments or aspirations, and the absence of intervention in the political rights of citizens. Political literacy has a significant impact on increasing forms of political participation and influences strengthening democracy.